Links Between Finance and University Organization: Comparative Analysis Spanish University - Fernández López, Sara (Education Policy Analysis Archives, 2004)
Over the last two decades serious problems have arisen in the modus operandi of higher education institutions. Some national governments are trying to solve them through policies to introduce or further promote market strategies in the management of the higher education organizations. The outcomes of these measures are not known yet but it seems that the marketization of higher education is inevitable. Spanish universities are not an exception in this process although it has been slow in comparison with other institutions in Europe; during the 1990s funding through contract-programs or quality evaluation was introduced in order to promote the move towards a better covering of societal needs. In December, 2001, the Organic Law for the Universities was enacted with the explicit purpose of enhancing institutional differences and the consequent competition among institutions. This article discusses the degree of marketization of Spanish universities and compares such processes with the changes occurring in the Netherlands. For this comparison economic policies and universities? degrees of autonomy are specially considered.